When high work engagement is negative for family tasks: mechanisms and boundary conditions - Onyishi, Ike E.; Nohe, Christoph; Ugwu, Fabian O.; Amazue, Lawrence O.; Hertel, Guido (Frontiers in Psychology, 2024)
Typically, work engagement is positively related to beneficial job outcomes. Earlier studies, however, revealed a "dark side" of work engagement showing negative effects such as more work-family conflict. Using a resource perspective, our study seeks to better understand why and when these negative effects of work engagement occur. Specifically, we test a new model in which the relationship of work engagement with work-family conflict is mediated by organizational citizenship behavior (OCB) and work rumination. Moreover, we argue that employees' resource-building strategies (i.e., job crafting) and resource levels (i.e., psychological capital) buffer resource depletion due to high work engagement. We test our assumptions in a field study that involved data collected on three measurement points with 523 employees from Nigeria. Results from latent structure equation modelling confirm that work rumination mediates the positive relationship between work engagement and work-family conflict. Additionally, our findings suggest that behavioral engagement (i.e., OCB) and work rumination serially mediate the relationship between work engagement and work-family conflict. Moreover, psychological capital mitigated the relationships of work engagement with work rumination, but not job crafting. Our study helps to understand better the "dark side" of work engagement and offers implications on how to mitigate its detrimental relationship with work-family conflict.